Connecting sponsor brands through sports competitions: an identity approach to brand trust and brand loyalty. Issue 2 (14th August 2020) - Pan, Po-Lin; Phua, Joe
Abstract : Purpose: The purpose of this paper was to examine the interplay between sports fanship and brand-related perceptions in the context of sports sponsorship. The effects of sport fans' self-enhancement strategies: Basking in reflected glory (BIRGing) and cutting off reflected failure (CORFing) were investigated in response to how sports fans connected themselves to a sponsor brand as well as whether their sponsor brand trust and loyalty were activated. Design/methodology/approach: An experiment was designed in the first study to examine immediate effects of team performance and sports fandom on sports fans' connection to the sponsor brand, while an online survey was conducted in the second study to investigate the joint effects of team performance and game venue on sports fans' sponsor brand trust and loyalty. Findings: The first study found that both team performance and sports fandom yielded significant effects on sports fans' connection to the sponsor brand. Specifically, sports fans with higher fandom reported the highest connection to the sponsor brand after the success of their favorite team, while others with lower fandom exhibited the lowest connection after the failure of their favorite team. The second study suggested that team performance and game venue yielded both main and joint effects on sponsor brand trust and loyalty. Moreover, fan identification mediated the joint effects of team performance and game venue on both sponsor brand trust and loyalty. Originality/value: Replicating the concepts of BIRGing and CORFing into the context of sports sponsorship, this paper verified the vigorous roles of BIRGing and CORFing in influencing sports fans' perceptions of the sponsor brand. Moreover, both theoretical and practical insights into BIRGing and CORFing concepts applicable to examine the impact of the fan–team relationships on sport fans' perceptions of the sponsor brand through sports sponsorship would be generated for the advancement of sports business research.